Transportability of imagery-enhanced CBT for social anxiety disorder. (July 2018) - McEvoy, Peter M.; Erceg-Hurn, David M.; Barber, Kevin C.; Dupasquier, Jessica R.; Moscovitch, David A.
Abstract: Pilot and open trials suggest that imagery-enhanced group cognitive behaviour therapy (CBT) is highly effective for social anxiety disorder (SAD). However, before being considered reliable and generalisable, the effects of the intervention need to be replicated by clinicians in a setting that is independent of the protocol developers. The current study compared outcomes from clients with a principal diagnosis of SAD at the Australian clinic where the protocol was developed (n = 123) to those from an independent Canadian clinic (n = 46) to investigate whether the large effects would generalise. Trainee clinicians from the independent clinic ran the groups using the treatment protocol without any input from its developers. The treatment involved 12 2-h group sessions plus a one-month follow-up. Treatment retention was comparable across both clinics (74% vs. 78%, ≥9/12 sessions) and the between-site effect size was very small and non-significant on the primary outcome (social interaction anxiety, d  = 0.09, p  = .752). Within-group effect sizes were very large in both settings ( d s = 2.05 vs. 2.19), and a substantial minority (41%–44%) achieved clinically significant improvement at follow-up. Replication of treatment effects within an independent clinic and with trainee clinicians increases confidence that outcomes are generalisable. Highlights: Imagery-enhanced group CBT for social anxiety disorder was evaluated. Outcomes were compared across the Australian development site and an independent Canadian clinic. Effect sizes, trajectories of change, and rates of clinically significant change were similar. Unadjusted and adjusted (propensity score matching) analyses yielded similar findings. Imagery-enhanced group CBT appears transportable to independent clinics with trainee therapists.